Association Between CRISPLD2 Polymorphisms and the Risk of Nonsyndromic Clefts of the Lip and/or Palate: A Meta-analysis. (March 2018) - Ge, Xing; Shi, Qiao-Mei; Ding, Zhen; Ju, Qiang; Wang, Hui; Wang, Qi; Li, Meng-Xue; Chen, Gang; Wang, Heng-Xue; Xu, Li-Chun
Objective: Nonsyndromic clefts of the lip and/or palate (NSCL/P) are one of the most common polygenic diseases. Recently, many studies focused on the association between CRISPLD2 polymorphisms and NSCL/P risk. However, some studies have shown opposite results. In this study, meta-analysis was used to confirm whether CRISPLD2 polymorphism was associated with NSCL/P, and the possible mechanism between CRISPLD2 and NSCL/P was explored. Methods: Relevant studies were conducted on PubMed, Ovid, EBSCO, CINAHL, FMRS, Web of Science, CNKI, and Wanfang databases from their inception up to June 31, 2016. Review Manager 5.0.24 was used to analyze whether CRISPLD2 polymorphism was involved in NSCL/P by pooling odds ratios (ORs) and 95% confidence intervals (CIs). Potential publication bias was evaluated by visual inspection of the funnel plot. Results: CRISPLD2 rs4783099 was associated with cleft lip and/or palate (CL/P) statistically (OR = 3.18, P < .01). Compared to genotype TT, genotypes CC and CT were correlated significantly (OR = 2.04, P = .04) with CL/P. No evidence showed an association between genetic variation at the CRISPLD2 locus and cleft palate only (CP). Conclusion: The polymorphism of CRISPLD2 rs4783099 is correlated with an increased risk of CL/P.